Real-time terahertz digital holography with a quantum cascade laser - Locatelli, Massimiliano (Sci Rep, 2015)
Coherent imaging in the THz range promises to exploit the peculiar capabilities of these wavelengths to penetrate common materials like plastics, ceramics, paper or clothes with potential breakthroughs in non-destructive inspection and quality control, homeland security and biomedical applications. Up to now, however, THz coherent imaging has been limited by time-consuming raster scanning, point-like detection schemes and by the lack of adequate coherent sources. Here, we demonstrate real-time digital holography (DH) at THz frequencies exploiting the high spectral purity and the mW output power of a quantum cascade laser combined with the high sensitivity and resolution of a microbolometric array. We show that, in a one-shot exposure, phase and amplitude information of whole samples, either in reflection or in transmission, can be recorded. Furthermore, a 200 times reduced sensitivity to mechanical vibrations and a significantly enlarged field of view are observed, as compared to DH in the visible range. These properties of THz DH enable unprecedented holographic recording of real world dynamic scenes.